Effects of the Phase Interface on Spallation Damage Nucleation and Evolution in Dual‐Phase Steel. Issue 6 (20th February 2020) - Yang, Yang; Wang, Haimin; Wang, Can; Yang, Luwei
Abstract : The dual‐phase steel sample obtained by step quenching (SQ) of AISI 1020 steel is shock loaded using one‐stage light‐gas gun experiments. The free surface particle velocity is measured by Doppler pin system (DPS) during the loading experiment. The effect of phase interface on spallation damage nucleation and evolution in dual‐phase steel is investigated with optical microscopy (OM), nanoindentation, and electron backscatter diffraction (EBSD) techniques. The evolution mechanism of spallation damage in dual‐phase steel is systematically analyzed. The results show voids nucleated within martensite rather than at the martensite/ferrite interface under dynamic loading. The nucleation of voids in martensite was not random, the martensite block boundaries with a great Taylor Factor (TF) mismatch and a large angle to the impact direction were the preferred nucleation positions of the voids. Voids nucleate, grow and further coalesce into microcracks. Most of the microcracks propagate across the phase interface and the propagation direction hardly deflects. Due to the existence of many martensite blocks with high‐angle grain interface boundaries inside the martensite, the resistance of microcracks propagation in martensite is greater than that in ferrite. Furthermore, the size of microcracks is related to the angle between the direction of martensite blocks and shock direction. Abstract : Due to the effect of martensite/ferrite phase interface on shock waves, voids nucleate within martensite under shock loading. In martensite, the block boundaries with a great Taylor factor (TF) mismatch are the preferred nucleation positions. Voids grow, coalesce, and finally form into microcracks. Microcracks cross through phase interface and propagate along its original direction and finally form into transgranular cracks.